Integrative-Contextual Curriculum Management in Maintaining the Existence of Modern Islamic Boarding Schools in Manbaul 'Alaa Grobogan - Witanti, Fitria Nita; Sukardi, Imam Sukardi; Baidi, Baidi Baidi (Pascasarjana IAIN Kudus, 2025)
This study aims to comprehensively analyse the implementation of an integrative-contextual curriculum management in maintaining the existence of Manbaul ‘Alaa Islmaic Boarding School as an Islamic educational institution oriented towards the formation of spiritual, moral, and intellectual intelligence of students amid the dynamics of socio-global change. Adopting a descriptive qualitative approach involving observation, in-depth interviews, and document analysis, the study identifies strategies for aligning the national and Diniyah curricula, incorporating Islamic values into general learning, and cultivating an academic culture reflective of contemporary boarding schools. The results demonstrate the successful implementation of vision-based curriculum planning, collaborative learning supervision, and teacher capacity building to manage integrative learning that emphasises character, manners, and modern literacy. Supporting factors include visionary leadership, religious culture, and community partnerships, while obstacles include limited availability of integrative teachers, adapting educational technology, and the burden of a dual curriculum. This research’s original contribution lies in mapping an integrative-contextual curriculum management model based on Islamic values, which is relevant to 21st-century needs, and which has been developed through a grounded approach to educational practices in modern Islamic boarding schools. This model can serve as a reference for other Islamic boarding schools when designing a curriculum system that balances general knowledge and Islamic scholarship while preserving cultural identity. The research also provides practical recommendations in the form of mechanisms for improving the competence of integrative teachers, a character- and global competency-based framework for evaluating curricula, and a plan to strengthen modern Islamic boarding schools’ social and digital collaboration to enhance institutional competitiveness. Therefore, an integrative-contextual curriculum management approach is valuable tool for maintaining the continuity, legitimacy, and sustainability of modern Islamic educational institutions during a period of educational transformation.Keywords: Curriculum Management, Integrative-Contextual, Modern Islamic Boarding School, Islamic Education, Existence